The role of market share and portfolio share based auditor specialization on audit fees - Azahra, Fatimah; Wardhani, Marita Kusuma (Proceeding International Conference on Accounting and Finance, 2024)
This study aims to determine the effect of Auditor Specialization based on Market Share and Portfolio Share on Audit Fee in companies listed on the Indonesia Stock Exchange with control variables, namely Company Size, Institutional Ownership, KAP Big4, Audit Tenure, and Auditor Opinion. The sample population of this study is a company listed on the Indonesia Stock Exchange in 2020 - 2022. This study uses purposive sampling technique as a sampling method. The number of samples in this study were 37 companies for 3 years. The results showed that auditor specialization base on Market Share (ISP 1) have a significant positive effect on Audit Fee in company listed at IDX at the 0.05 significance level. The variables of Portofolio Share (ISP 2) have no effect on Audit Fee in company listed at IDX at a significance level of 0.05.This research can be useful for companies in selecting auditors and for further research